Learning Media in The Perspective of Elementary School/Madrasah Ibtidaiyah Teachers - Hidayat, Imam Wahyu; Firmantika, Lusty (Prodi PGMI IAIN Salatiga, 2020)
The teachers are the main actors in developing learning. Learning is said to be successful if it achieves goals. Learning achievement occurs if supported by good facilities and infrastructure, one of which is learning media. The ideal learning media is developed by teachers who have broad perspectives. This research's objectives are knowing the perspective of SD/MI teachers on learning media, knowing the form of media used by SD/MI teachers in learning, knowing the form of media developed by the teacher. This study uses a qualitative method with a phenomenological approach. The research data were collected through a Focus Group Discussion (FGD). Data were analyzed using the Miles and Huberman model. The results of this study indicate that: 1. The teacher still interprets the learning media as the result of sophisticated modern technology but does not have a broad meaning; 2. The learning media used are still limited to modern technology, not optimally utilizing simple technology, the potential of the surrounding environment, or the three's collaboration; 3. The learning media developed are still limited to modern technology results, have not utilized simple technology, the potential of the surrounding environment, or the three's collaboration.